2016
DOI: 10.1063/1.4942476
|View full text |Cite
|
Sign up to set email alerts
|

Magnetohydrodynamic flow of Sisko fluid over a stretching cylinder with variable thermal conductivity: A numerical study

Abstract: In present study effects of magnetic field and variable thermal conductivity on Sisko fluid model are analyzed. The modeled partial differential equations are simplified by boundary layer approach. Appropriate similarity transformations are applied to transform governing partial differential equations into ordinary differential equations. Then these equations are solved numerically by shooting method in combination with Runge-Kutta-Fehlberg method. Comparison between present and previous computed results is pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Khan and Shahzad 26 used the homotopy analysis method to investigate the boundary layer flow of a Sisko fluid model over a stretched sheet. Using a Sisko fluid model with variable thermal conductivity and viscous dissipation, Malik et al and Hussain et al 27,28 examined the impact of MHD and heat transmission over a stretching cylinder. The Runge-Kutta-Fehlberg method was used to modify the fundamental equations, and they found that temperature rises with thermal conductivity and curvature parameter.…”
Section: Introductionmentioning
confidence: 99%
“…Khan and Shahzad 26 used the homotopy analysis method to investigate the boundary layer flow of a Sisko fluid model over a stretched sheet. Using a Sisko fluid model with variable thermal conductivity and viscous dissipation, Malik et al and Hussain et al 27,28 examined the impact of MHD and heat transmission over a stretching cylinder. The Runge-Kutta-Fehlberg method was used to modify the fundamental equations, and they found that temperature rises with thermal conductivity and curvature parameter.…”
Section: Introductionmentioning
confidence: 99%
“…Salahuddin et al [18] discussed the impact of thermal conductivity using a stretching cylinder. Malik et al [19] discussed the effect of MHD Sisko fluid using a stretching cylinder. For energy properties, nanofluids are the active representatives.…”
Section: Introductionmentioning
confidence: 99%
“…The Sisko fluid model is one of the most important fluid models portraying the flow in the power‐law and upper Newtonian regions. The aforementioned model is most appropriate to describe the flow behavior of fluids in high shear rate regions.…”
Section: Introductionmentioning
confidence: 99%